2019
DOI: 10.21829/abm126.2019.1458
|View full text |Cite
|
Sign up to set email alerts
|

Safe microsites for Symphoricarpos microphyllus (Caprifoliaceae) germination, a shrub species with seed dormancy

Abstract: Background and Aims: Temperate forests suffer continuous deforestation and other anthropogenic disturbances. Additionally, some types of forest management, such as secondary vegetation removal ("chaponeo"), can be another disturbance that negatively affects the values of some environmental variables important for seed germination. Light, soil temperature and moisture characterize microsites and determine germination percentages. These variables are also affected by slope orientation and vegetation structure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…However, GSF did show significant effects for A. glabrata meaning that as most secondary species, it is highly responsive to gap openings (Redwood et al, 2016), In terms of the light requirements for the germination of both species, S. angulifolius showed the highest germination percentages in FR light conditions in growth chambers. Other shrub species in this study area have been reported to germinate in high percentages in FR light as well (Martínez-Camacho et al, 2018;Martínez-Orea et al, 2019). In field conditions, germination was the highest for both species at US microsites, where RL values were higher than FRL.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…However, GSF did show significant effects for A. glabrata meaning that as most secondary species, it is highly responsive to gap openings (Redwood et al, 2016), In terms of the light requirements for the germination of both species, S. angulifolius showed the highest germination percentages in FR light conditions in growth chambers. Other shrub species in this study area have been reported to germinate in high percentages in FR light as well (Martínez-Camacho et al, 2018;Martínez-Orea et al, 2019). In field conditions, germination was the highest for both species at US microsites, where RL values were higher than FRL.…”
Section: Discussionmentioning
confidence: 60%
“…Although seeds were sown when mature and right after collection and during dispersal times, the best temperatures for germination are most likely reached in June, when temperatures of 20-25°C have been recorded (Vázquez-Santos et al, 2019 in press) at this study site and when soil moisture values reach 100%, during the onset of the rainy season, therefore seed germination can vary between seasons independently from seed maturity (Baskin and Baskin, 1998). Although seeds of many species will germinate at constant temperatures, the germination of many shrub species increases due to temperature fluctuations (Zambino, 2010;Martínez-Orea et al, 2019). Another factor that could explain the low germination percentages registered could be the presence of primary seed dormancy.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations